Implementation of ICT (Information, Communication, and Technology) Based Fiqih Learning in Class XII of Madrasah Alyah Ar-Raudhatul Hasanah Medan - Arief Fikri; Nahar, Syamsu (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2022)
material provided by the fiqh teachers to be more effective and efficient, it is necessary to apply learning that can motivate and stimulate students to be enthusiastic in learning. One of them is by utilizing ICT (information, communication, and technology) or ICT-based learning media (information, communication, and technology) or what we often call ICT (technology, information, and communication). This study aims to explain how the implementation of ICT-based learning media (information, communication, and technology) in the learning process of fiqh education in madrasah aliyah. This research method is qualitative research. The nature of this research is descriptive, namely regular decomposition analysis, so the whole concept of providing understanding and explanation to get a description of the results. The data analysis that the writer uses in this research is an analysis of the tracking process and systematic arrangement, field notes that the authors have obtained from interviews, observations and other materials so that the authors can report the results of the research. The results of this author's qualitative research are: (1) The implementation of ICT-based fiqh learning (information, communication, and technology) in class XII Madrasah Aliyah Pesantren Ar-Raudhatul Hasanah Medan City, (2) The implementation of ICT media (information, communication, and technology) focusing on Fiqh lessons in Class XII Madrasah Aliyah Pesantren Ar-Raudhatul Hasanah Medan City, (3) There are supporting and inhibiting factors in the implementation of fiqh learning by using ICT (information, communication, and technology) utilizing infocus media in class XII Madrasah Aliyah Pesantren Ar-Raudhatul Hasanah Medan City